Health professionals' experiences of behavioural family therapy for adults with intellectual disabilities: a thematic analysis. Issue 5 (June 2017) - Hutchison, J.; Lang, K.; Anderson, G.; MacMahon, K.
Accessible summary: What is known on the subject?: Behavioural Family Therapy (BFT) has been shown to help people with some severe mental health conditions, such as schizophrenia, by reducing relapse rates and stress within families. It can be difficult to put family interventions, like BFT, into clinical practice. Families where someone has an intellectual disability can experience more stress compared to those who do not, but we know very little about using BFT with families where a member has an intellectual disability. What this paper adds to existing knowledge?: We interviewed nine Community Learning Disability Nurses and Allied Health Professionals about their experiences delivering BFT to families where one member has an intellectual disability. We found that therapists' experiences of delivering BFT were broadly positive, although they found some aspects of their service frustrating. Explain the importance of the paper's findings for a non‐specialist audience: The study identifies the perceived benefits of BFT as a model to work with families, where a member has an intellectual disability. The study highlights some of the challenges experienced by practitioners, notably issues with engagement and some issues specific to working with adults with an intellectual disability. The findings suggest that it needs to be clear which families would benefit most from BFT, that interventions need to be adapted for people with intellectual disabilities and that Community Learning Disability Nurses and Allied Health Professionals should have support from management to deliver these interventions. Abstract: Introduction: Studies have found family interventions (FIs) to be effective in reducing stress and relapse rates for a variety of mental health conditions. However, implementing FIs into clinical practice is challenging. Studies have suggested that levels of stress within some families of people with intellectual disabilities can be high. However, there is little reported about the use and implementation of FIs, such as Behavioural Family Therapy (BFT), in adult intellectual disability services. Purpose of study: To explore the experiences of practitioners delivering BFT to adults with intellectual disabilities. Method: A qualitative methodology was employed, using semi‐structured individual interviews with BFT therapists from a health professional background ( n  = 9). Data were analysed thematically. Results: Two overarching themes were identified: positivity and frustration. Discussion: Implementation of therapy was identified as being broadly successful but with some underlying challenges, notably wider organizational issues and some issues specific to working with adults with intellectual disabilities. Implications for practice: The broadly positive experiences reported provide encouragement for the delivery of FIs, such as BFT, to adults with intellectual disabilities, by professions outwith psychology. However, there is a need to provide clarity on referral processes, adapt materials accordingly for this client group and ensure that supportive management and supervision is available to therapists.